High-matching-degree concrete shrinkage compensation additive and application thereof

By combining aluminoferrite mineral powder and a modifier, the problems of time-sensitivity and resource dependence in concrete shrinkage compensation technology have been solved, achieving efficient and environmentally friendly concrete shrinkage compensation and improving the density and mechanical properties of concrete.

CN120923165AActive Publication Date: 2025-11-11UNIV OF JINAN

Patent Information

Application Number
CN202511462466.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-14
Publication Date
2025-11-11
Estimated Expiration
2045-10-14

AI Technical Summary

Technical Problem

Existing concrete shrinkage compensation technologies suffer from problems such as time-sensitivity imbalance, high cost, and large carbon emissions. Traditional expansion agents cannot effectively compensate for drying shrinkage and rely on natural mineral resources.

Method used

By combining aluminoferrite mineral powder and a modifier, and by controlling expansion in stages, using industrial solid waste as raw material, a high-matching concrete shrinkage compensation additive is prepared. This additive utilizes the synergistic effect of aluminoferrite mineral powder and a modifier to provide stepwise and controllable dissolution of SO42-, thereby matching the expansion aging with the concrete hydration process.

Benefits of technology

This approach achieves a match between expansion aging and the concrete hydration process, improving the density and mechanical properties of concrete, reducing costs, and decreasing carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120923165A_ABST
    Figure CN120923165A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of concrete materials, and particularly discloses a high-matching-degree concrete shrinkage compensation additive and application thereof. The additive comprises the following components in parts by weight: 3-20 parts of aluminoferrite mineral powder and 6-26 parts of a modified regulating agent. Wherein the preparation of the modified regulating agent comprises the following steps: (1) mixing a composite modifier composed of dihydrate gypsum powder, a regulating agent and sulfate, calcining in stages, and quenching after the calcination is completed, so as to obtain the beta-type modified semi-hydrated gypsum. And (2) uniformly mixing the beta-type modified semi-hydrated gypsum with anhydrous gypsum powder, then uniformly mixing the obtained mixed powder with liquid polyethylene glycol, standing and aging to obtain the modified regulating agent. According to the high-matching-degree concrete shrinkage compensation additive, expansion can be precisely regulated and controlled in stages, and the adopted industrial solid waste serves as the raw material, so that the cost is reduced, and resource utilization is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete materials technology, specifically to a high-compliance concrete shrinkage compensation additive and its application. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] Concrete, as the most widely used building material globally, directly affects the durability and safety of engineering structures. However, concrete shrinkage, an inherent volumetric deformation phenomenon, has long been a key cause of structural cracking and shortened service life. This is because during the hardening process, shrinkage caused by moisture migration, chemical reactions, and temperature changes (such as plastic shrinkage, drying shrinkage, autogenous shrinkage, and carbonation shrinkage) generates internal tensile stress. When this stress exceeds the tensile strength of the concrete, cracks form, accelerating the intrusion of harmful substances such as chloride ions and carbon dioxide, and inducing steel corrosion. This problem is particularly prominent in marine environments or areas with freeze-thaw cycles.

[0004] In recent years, with the development of super-long and super-high-rise building structures, solving the problem of concrete shrinkage cracking has become increasingly important. Existing concrete shrinkage compensation technologies mainly rely on single or compound admixtures of expansive agents, shrinkage reducers, and fibers, which suffer from shortcomings such as unbalanced effectiveness and lack of sustainability. Traditional calcium sulfoaluminate and calcium oxide expansive agents focus on early expansion and easily cause stress concentration, while their expansion energy depletes after 28 days, failing to compensate for drying shrinkage. Therefore, these traditional expansive agents generally suffer from a mismatch between the timeliness of shrinkage compensation and concrete shrinkage due to premature depletion. Furthermore, existing expansive agents largely rely on natural mineral resources, resulting in high raw material costs and significant carbon emissions during production, which is detrimental to achieving emission reduction targets. Summary of the Invention

[0005] To address the aforementioned problems, this invention discloses a high-matching concrete shrinkage compensation additive and its application. It not only enables precise, phased control of expansion, but also utilizes industrial solid waste as a raw material, which helps reduce costs and achieve resource utilization. Specifically, the technical solution of this invention is as follows.

[0006] First, this invention discloses a high-matching concrete shrinkage compensation additive, comprising the following components in the following proportions: 3-20 parts by weight of aluminoferrite mineral powder and 6-26 parts by weight of a modifier. The modifier is composed of microparticles formed from β-type modified hemihydrate gypsum, an anhydrous gypsum core, and polyethylene glycol loaded on the surface of the core, wherein the β-type modified hemihydrate gypsum contains a portion of its Ca... 2+K + and / or Al 3+ Lattice distortion resulting from substitution.

[0007] Furthermore, the aluminoferrite minerals consist of Ca2Al minerals with gradually increasing aluminum content. 0.21 Fe 1.79 O5, Ca2Al 0.6 Fe 1.4 O5 and Ca2Al 1.07 Fe 0.93 Composed of O5. Optionally, the Ca2Al 0.21 Fe 1.79 O5, Ca2Al 0.6 Fe 1.4 O5, Ca2Al 1.07 Fe 0.93 The mass ratio of O5 is 1~2.5:1.5~3.5:2~4.

[0008] Furthermore, the specific surface area of ​​the aluminoferrite mineral powder is not less than 400 m². 2 / kg.

[0009] Furthermore, the particle size of the modified regulator is 45~80μm.

[0010] Furthermore, the preparation of the modified regulator includes the following steps: (1) After mixing gypsum dihydrate powder and a composite modifier consisting of regulator and sulfate, the mixture is calcined in stages and then rapidly cooled to obtain β-type modified hemihydrate gypsum; the regulator is composed of polycarboxylate superplasticizer and lignin sulfonate.

[0011] (2) Mix the β-type modified hemihydrate gypsum with anhydrous gypsum powder, then mix the resulting mixed powder with liquid polyethylene glycol, and let it stand for aging to obtain the modified regulator.

[0012] Further, in step (1), the composite modifier is 0.5-3.0% of the mass of dihydrate gypsum powder. Optionally, the dihydrate gypsum includes at least one of desulfurized gypsum, natural gypsum, phosphogypsum, titanium gypsum, etc.

[0013] Furthermore, the mass ratio of the polycarboxylate superplasticizer, lignin sulfonate, and sulfate is 0.3~1:0.1~0.5:0.2~1.0.

[0014] Further, in step (1), the sulfate includes at least one of aluminum sulfate, potassium sulfate, etc.

[0015] Further, in step (1), the lignin sulfonate includes at least one of sodium lignin sulfonate, calcium lignin sulfonate, etc.

[0016] Further, in step (1), the staged calcination process includes: first, preheating and dehydration at 120~140℃ for 10~20min, and then raising the temperature to 160~180℃ and holding for 30~50min. Optionally, after calcination, the temperature is rapidly cooled to below 60℃.

[0017] Further, in step (2), the mass ratio of the β-type modified hemihydrate gypsum to anhydrous gypsum powder is 1~6:2~8. Optionally, the anhydrous gypsum includes at least one of natural anhydrite, fluorogypsum, etc.

[0018] Further, in step (2), the liquid polyethylene glycol accounts for 1.0~1.5% of the mass of the mixed powder. Optionally, the molecular weight of the liquid polyethylene glycol is not greater than 600.

[0019] Furthermore, in step (2), the settling and aging time is 20 to 24 hours.

[0020] Secondly, this invention discloses the application of the high-matching concrete shrinkage compensation additive in concrete materials. Optionally, the additive is 3-15% of the mass of the cementitious components (such as cement, fly ash, silica fume, etc.) in the concrete material.

[0021] Compared with the prior art, the present invention has at least the following beneficial technical effects: (1) This invention uses three iron aluminate minerals, Ca2Al, with gradually increasing aluminum content. 0.21 Fe 1.79 O5, Ca2Al 0.6 Fe 1.4 O5 and Ca2Al 1.07 Fe 0.93 O5 and other elements together form an expansion source. As the aluminum content increases, the difference in the increase of the ratio of [AlO4] / [FeO4] and [AlO6] / [FeO6] becomes more significant, resulting in different hydration activities. This invention utilizes the aforementioned Ca2Al 1.07 Fe 0.93 O5, Ca2Al 0.6 Fe 1.4 O5 and Ca2Al 0.21 Fe 1.79 O5 plays a role in the early, middle, and late stages of concrete hydration, compensating for shrinkage during these periods and achieving a match between expansion aging and microcrack formation. Furthermore, due to the presence of Ca2Al... 0.21 Fe 1.79 O5 has a slow hydration rate, and Ca2Al can be used when shrinkage cracks occur in the later stages of concrete hydration. 0.21 Fe 1.79O5 continues to react with moisture to hydrate, achieving self-repair of microcracks.

[0022] (2) This invention utilizes the different dissolution rates of β-type modified hemihydrate gypsum and anhydrous gypsum in the modified regulator to achieve SO4 2- The gradual and controlled dissolution allows the hemihydrate gypsum to initially provide SO4 during the early stages of concrete hydration. 2- To avoid the problem of microcracks caused by a sudden increase in early expansion, SO4 is continued to be supplied through the anhydrous gypsum in the later stage. 2- This inhibits the phase transition of the expansion product AFt to monosulfide-type hydrated calcium sulfoaluminate (AFm) due to its instability, preventing expansion degradation caused by premature depletion of sulfate ions. Therefore, the synergistic effect of the modified regulator and the aluminoferrite minerals ensures both SO42- and SO42-level stability. 2- The continuous supply of nutrients, along with the full utilization of Al2O3 and Fe2O3 in the aluminoferrite minerals, generates a more stable expansion product AFt, achieving sustained nucleation and growth of the expansion product during the critical shrinkage compensation period. This ensures that the formation rate of the expansion product matches the hydration process of the concrete. Simultaneously, the β-type modified hemihydrate gypsum and anhydrous gypsum rehydrate during cement hydration to form dihydrate gypsum, resulting in volume expansion and achieving more effective compensation. Furthermore, the hydration of the aluminoferrite minerals can also generate iron glue (Fe(OH)3), which can fill the pores, further increasing the density of the concrete and contributing to strength improvement.

[0023] (3) In this invention, polyethylene glycol uses its ether bonds to chelate with Ca²⁺ provided by hemihydrate gypsum in the core of the modified regulator to form a hydrophilic layer, which destroys the hydrogen bond network between the hemihydrate gypsum crystals and reduces the aggregation barrier. This allows the modified regulator to be more uniformly dispersed in concrete and to better play its role in compensating for shrinkage.

[0024] (4) This invention also utilizes the regulator and sulfate to prepare β-type modified hemihydrate gypsum, wherein the polycarboxylate superplasticizer in the regulator plays a role in regulating crystal morphology, inhibiting the axial growth of the formed β-type modified hemihydrate gypsum crystals, reducing their aspect ratio, eliminating stress concentration sources, and refining the size of gypsum crystals. This not only serves as a nucleation site for hydration products but also refines the capillary pore structure, thereby reducing concrete porosity and improving mechanical properties. Simultaneously, this invention also utilizes the lignin sulfonate adsorbed on the surface of dihydrate gypsum particles to reduce interfacial energy and prevent particle agglomeration. The accelerator replaces Ca in the dihydrate gypsum. 2+ Constructing lattice distortion reduces the phase transition energy barrier and increases the rate of water removal from gypsum dihydrate during the staged calcination process, which is beneficial for obtaining the target product. Attached Figure Description

[0025] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Hereinafter, embodiments of the invention will be described in detail with reference to the accompanying drawings, wherein: Figure 1 The image shows a sample of the modified regulator prepared in Example 1 below.

[0026] Figure 2 The image shows a sample of the shrinkage compensation additive prepared in Example 1 below.

[0027] Figure 3 The image shows the XRD results of the shrinkage compensation additive prepared in Example 1 below.

[0028] Figure 4 The following is a 7-day expansion rate test graph for Example 1.

[0029] Figure 5 The following is a graph showing the 28-day compressive strength test results for Example 1.

[0030] Figure 6 The image shows a sample of the modified regulator prepared in Example 2 below.

[0031] Figure 7 The image shows a sample of the shrinkage compensation additive prepared in Example 2 below.

[0032] Figure 8 The following is a 7-day expansion rate test graph for Example 2.

[0033] Figure 9 The image shows a sample of the modified regulator prepared in Example 3 below.

[0034] Figure 10 The image shows a sample of the shrinkage compensation additive prepared in Example 3 below.

[0035] Figure 11 The following is a 7-day expansion rate test graph for Example 3.

[0036] Figure 12 The image shows a sample of the shrinkage compensation additive prepared in Example 4 below.

[0037] Figure 13 The image shows the XRD results of the shrinkage compensation additive prepared in Example 4 below.

[0038] Figure 14 The image shows a sample of the modified regulator prepared in Example 5 below.

[0039] Figure 15 The image shows a sample of the shrinkage compensation additive prepared in Example 5 below.

[0040] Figure 16 The image shows the XRD results of the shrinkage compensation additive prepared in Example 5 below.

[0041] Figure 17 The image shows a sample of the modified regulator prepared in Example 6 below.

[0042] Figure 18 The image shows a sample of the shrinkage compensation additive prepared in Example 6 below.

[0043] Figure 19 The image shows a sample of the modified regulator prepared in Example 7 below.

[0044] Figure 20 The image shows a sample of the shrinkage compensation additive prepared in Example 7 below.

[0045] Figure 21 The image shows a sample of the modified regulator prepared in Example 8 below.

[0046] Figure 22 The image shows a sample of the shrinkage compensation additive prepared in Example 8 below. Detailed Implementation

[0047] The present invention is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer.

[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of skill in the art. The reagents and raw materials used in this invention are readily available through conventional means, and unless otherwise specified, they shall be used in accordance with conventional methods or product instructions. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this invention. The preferred embodiments and materials described herein are for illustrative purposes only.

[0049] Example 1: A method for preparing a high-matching concrete shrinkage compensation additive, comprising the following steps: (1) Mix polycarboxylate superplasticizer, sodium lignosulfonate and aluminum sulfate in a mass ratio of 0.5:0.3:0.6 and grind them into powder to obtain a composite modifier for later use.

[0050] (2) Add 2% by weight of the composite modifier to the gypsum dihydrate (phosphogypsum) powder and stir until uniform. Then heat to 135°C and hold for 15 minutes, then heat to 170°C and hold for 45 minutes. After completion, cool rapidly to room temperature in air to obtain β-type modified hemihydrate gypsum for later use.

[0051] (3) The β-type modified hemihydrate gypsum and anhydrous gypsum (natural hard gypsum) powder were mixed at a mass ratio of 2:3 and stirred evenly to obtain a mixed powder with a particle size distribution between 45 and 80 μm. Then, polyethylene glycol (PEG-400) was sprayed into the mixed powder (PEG-400 was 1.5% of the mass of the mixed powder), and stirred in a mixer at a speed of 2000 rpm for 10 min. After completion, the product was transferred to a sealed container and allowed to stand for aging for 24 hours to obtain the modified regulator (such as...). Figure 1 (As shown), for later use.

[0052] (4) Take the following components in the following proportions: 14 parts by weight of aluminoferrite mineral powder and 15 parts by weight of the modifier described in this embodiment. The aluminoferrite mineral is composed of Ca2Al... 0.21 Fe 1.79 O5, Ca2Al 0.6 Fe 1.4 O5 and Ca2Al 1.07 Fe 0.93 The mixed powder formed by O5 in a mass ratio of 1.5:2:3 has a specific surface area of ​​401.7 m². 2 / kg. The above components were placed in a mixer and mechanically stirred for 3 minutes to obtain the high-matching concrete shrinkage compensation additive. The macroscopic sample image and XRD test results are shown below. Figure 2 , Figure 3 As shown.

[0053] Performance testing: (1) The shrinkage compensation additive prepared in this embodiment was added to cement mortar (formed by mixing 42.5 ordinary Portland cement, sand, and water in a mass ratio of 1:2:0.4) to make specimens. The dosage of the shrinkage compensation additive was 10% of the cement mass. Then, the restricted expansion rate of specimens at different ages (7d, 21d, and 56d) was tested according to the "Concrete Expansion Agent" (GB / T 23439-2017). (The 7d expansion rate test is as follows...) Figure 4 (2) The shrinkage compensation additive prepared in this embodiment is added to cement mortar (formed by 42.5 ordinary Portland cement: sand: water in a mass ratio of 1:3:0.5) to make specimens. The dosage of the shrinkage compensation additive is 10% of the cement mass. Then the 28-day compressive strength of the specimens is tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GBT 17671-2021). Figure 5 (As shown), the results are shown in the table below:

[0054] Example 2: A method for preparing a high-matching concrete shrinkage compensation additive, comprising the following steps: (1) Mix polycarboxylate superplasticizer, sodium lignosulfonate and aluminum sulfate in a mass ratio of 0.3:0.1:0.2 and grind them into powder to obtain a composite modifier for later use.

[0055] (2) Add 0.5% by weight of the composite modifier to the dihydrate gypsum (desulfurized gypsum) powder and stir evenly. Then heat to 120°C and keep warm for 20 minutes, then raise the temperature to 160°C and keep warm for 50 minutes. After completion, cool rapidly to room temperature in air to obtain β-type modified hemihydrate gypsum for later use.

[0056] (3) The β-type modified hemihydrate gypsum and anhydrous gypsum (natural hard gypsum) powder were mixed at a mass ratio of 1:2 and stirred evenly to obtain a mixed powder with a particle size distribution between 45 and 80 μm. Then, polyethylene glycol (PEG-400) was sprayed into the mixed powder (PEG-400 was 1.0% of the mass of the mixed powder), and stirred in a mixer at a speed of 1500 rpm for 20 min. After completion, the product was transferred to a sealed container and allowed to stand for aging for 24 hours to obtain the modified regulator (such as...). Figure 6 (As shown), for later use.

[0057] (4) Take the following components in the following proportions: 3 parts by weight of aluminoferrite mineral powder and 6 parts by weight of the modifier described in this embodiment. Wherein, the aluminoferrite mineral is composed of C2Al 0.21 Fe 1.79 O5, C2Al 0.6 Fe 1.4 O5, C2Al 1.07 Fe 0.93 The mixed powder formed by O5 in a mass ratio of 1:1.5:2 has a specific surface area of ​​526.4 m². 2 / kg. Place all the above components in a mixer and mechanically mix for 3 minutes to obtain a high-compliance concrete shrinkage compensation additive (such as...). Figure 7 (As shown).

[0058] Performance testing: (1) The shrinkage compensation additive prepared in this embodiment was added to cement mortar (same as in Example 1 above) to make specimens. The dosage of the shrinkage compensation additive was 3% of the cement mass. Then, the restricted expansion rate of specimens at different ages (7d, 21d, 56d) was tested according to the "Concrete Expansion Agent" (GB / T 23439-2017). Figure 8 (2) The shrinkage compensation additive prepared in this embodiment is added to cement mortar (same as in Example 1 above) to make specimens. The dosage of the shrinkage compensation additive is 3% of the cement mass. Then, the 28-day compressive strength of the specimens is tested according to GBT 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)". The results are shown in the table below:

[0059] Example 3: A method for preparing a high-matching concrete shrinkage compensation additive, comprising the following steps: (1) Mix polycarboxylate superplasticizer, calcium lignosulfonate and potassium sulfate in a mass ratio of 1.0:0.5:1.0 and grind them into powder to obtain a composite modifier for later use.

[0060] (2) Add 3% by weight of the composite modifier to the dihydrate gypsum (natural gypsum) powder and stir until uniform. Then heat to 140°C and hold for 10 minutes, then heat to 180°C and hold for 30 minutes. After completion, cool rapidly to room temperature in air to obtain β-type modified hemihydrate gypsum for later use.

[0061] (3) The β-type modified hemihydrate gypsum and anhydrous gypsum (fluorogypsum) powder were mixed at a mass ratio of 6:8 and stirred evenly to obtain a mixed powder with a particle size distribution between 45 and 80 μm. Then, polyethylene glycol (PEG-200) was sprayed into the mixed powder (PEG-200 was 1.2% of the mass of the mixed powder), and stirred in a mixer at a speed of 1200 rpm for 15 min. After completion, the product was transferred to a sealed container and allowed to stand for aging for 20 hours to obtain the modified regulator (such as...). Figure 9 (As shown), for later use.

[0062] (4) Take the following components in the following proportions: 20 parts by weight of aluminoferrite mineral powder and 26 parts by weight of the modifier described in this embodiment. Wherein, the aluminoferrite mineral is composed of Ca2Al 0.21 Fe 1.79 O5, Ca2Al 0.6 Fe 1.4 O5 and Ca2Al 1.07 Fe 0.93 The mixed powder formed by O5 in a mass ratio of 2.5:3.5:4 has a specific surface area of ​​478.2 m². 2 / kg. Place all the above components in a mixer and mechanically mix for 3 minutes to obtain a high-compliance concrete shrinkage compensation additive (such as...). Figure 10 (As shown).

[0063] Performance testing: (1) The shrinkage compensation additive prepared in this embodiment was added to cement mortar (same as in Example 1 above) to make specimens. The dosage of the shrinkage compensation additive was 15% of the cement mass. Then, the restricted expansion rate of specimens at different ages (7d, 21d, 56d) was tested according to the "Concrete Expansion Agent" (GB / T 23439-2017). Figure 11(2) The shrinkage compensation additive prepared in this embodiment is added to cement mortar (same as in Example 1 above) to make specimens. The amount of the shrinkage compensation additive is 15% of the cement mass. Then the 28-day compressive strength of the specimens is tested according to GBT 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)". The results are shown in the table below:

[0064] Example 4: A method for preparing a high-matching concrete shrinkage compensation additive, comprising the following steps: The following components are selected: 14 parts by weight of aluminoferrite mineral powder and 10 parts by weight of desulfurized gypsum powder. The aluminoferrite mineral is composed of C2Al... 0.21 Fe 1.79 O5, C2Al 0.6 Fe 1.4 O5, C2Al 1.07 Fe 0.93 The mixed powder formed by O5 in a mass ratio of 1.5:2:3 has a specific surface area of ​​401.7 m². 2 / kg. The above components were placed in a mixer and mechanically stirred for 3 minutes to obtain the high-matching concrete shrinkage compensation additive. The macroscopic sample image and XRD test results are shown below. Figure 12 , Figure 13 As shown.

[0065] Performance testing: The restricted expansion rate and compressive strength of the shrinkage compensation additive prepared in this embodiment were tested using the same method as in Example 1 above. The results are shown in the table below. A negative restricted expansion rate indicates that volume shrinkage has occurred.

[0066] Example 5: A method for preparing a high-matching concrete shrinkage compensation additive, comprising the following steps: (1) Mix polycarboxylate superplasticizer, calcium lignosulfonate and potassium sulfate in a mass ratio of 1.0:0.5:1.0 and grind them into powder to obtain a composite modifier for later use.

[0067] (2) Add 3% by weight of the composite modifier to the dihydrate gypsum (natural gypsum) powder and stir evenly. Then heat to 140°C and hold for 10 min, then heat to 180°C and hold for 30 min. After completion, cool rapidly to room temperature in air, and after sieving, obtain β-type modified hemihydrate gypsum with a particle size distribution between 45 and 80 μm for later use.

[0068] (3) Polyethylene glycol (PEG-200) was sprayed into the β-modified hemihydrate gypsum (PEG-200 was 1.2% of the mass of the β-modified hemihydrate gypsum), and stirred in a mixer at a speed of 1200 rpm for 15 min. After completion, the product was transferred to a sealed container and allowed to stand for aging for 20 hours to obtain the modifier (e.g., Figure 14 (As shown), for later use.

[0069] (4) Take the following components in the following proportions: 20 parts by weight of aluminoferrite mineral powder and 26 parts by weight of the modifier described in this embodiment. Wherein, the aluminoferrite mineral is composed of Ca2Al 0.21 Fe 1.79 O5, Ca2Al 0.6 Fe 1.4 O5 and Ca2Al 1.07 Fe 0.93 The mixed powder formed by O5 in a mass ratio of 2.5:3.5:4 has a specific surface area of ​​478.2 m². 2 / kg. The above components were placed in a mixer and mechanically stirred for 3 minutes to obtain the high-matching concrete shrinkage compensation additive. The macroscopic sample image and XRD test results are shown below. Figure 15 , Figure 16 As shown.

[0070] Performance testing: The restricted expansion rate and compressive strength of the shrinkage compensation additive prepared in this embodiment were tested using the same method as in Example 3 above. The results are shown in the table below. A negative restricted expansion rate indicates that volume shrinkage has occurred.

[0071] Example 6: A method for preparing a high-matching concrete shrinkage compensation additive, comprising the following steps: (1) Heat the gypsum dihydrate (phosphogypsum) powder to 135°C and hold for 15 minutes, then raise the temperature to 170°C and hold for 45 minutes. After completion, cool it rapidly in air to room temperature to obtain a solid product for later use.

[0072] (2) The solid product and anhydrous gypsum (natural hard gypsum) powder were mixed at a mass ratio of 2:3 and stirred evenly to obtain a mixed powder with a particle size distribution between 45 and 80 μm. Then, polyethylene glycol (PEG-400) was sprayed into the mixed powder (PEG-400 was 1.5% of the mass of the mixed powder), and stirred in a mixer at a speed of 2000 rpm for 10 min. After completion, the product was transferred to a sealed container and allowed to stand for aging for 24 hours to obtain a modifier (such as...). Figure 17 (As shown), for later use.

[0073] (3) Take the following components in the following proportions: 14 parts by weight of aluminoferrite mineral powder and 15 parts by weight of the modifier described in this embodiment. The aluminoferrite mineral is composed of C2Al 0.21 Fe 1.79 O5, C2Al 0.6 Fe 1.4 O5, C2Al 1.07 Fe 0.93 The mixed powder formed by O5 in a mass ratio of 1.5:2:3 has a specific surface area of ​​401.7 m². 2 / kg. Place all the above components in a mixer and mechanically mix for 3 minutes to obtain a high-compliance concrete shrinkage compensation additive (such as...). Figure 18 (As shown).

[0074] Performance testing: The restricted expansion rate and compressive strength of the shrinkage compensation additive prepared in this embodiment were tested using the same method as in Example 1 above. The results are shown in the table below. A negative restricted expansion rate indicates that volume shrinkage has occurred.

[0075] Example 7: A method for preparing a high-matching concrete shrinkage compensation additive, comprising the following steps: (1) Mix polycarboxylate superplasticizer, sodium lignosulfonate and aluminum sulfate in a mass ratio of 0.3:0.1:0.2 and grind them into powder to obtain a composite modifier for later use.

[0076] (2) Add 0.5% by weight of the composite modifier to the dihydrate gypsum (desulfurized gypsum) powder and stir evenly. Then heat to 120°C and keep warm for 20 minutes, then raise the temperature to 160°C and keep warm for 50 minutes. After completion, cool rapidly to room temperature in air to obtain β-type modified hemihydrate gypsum for later use.

[0077] (3) The β-type modified hemihydrate gypsum and anhydrous gypsum (natural anhydrite) powder are mixed at a mass ratio of 1:2 and stirred evenly to obtain a particle size regulator (such as...) with a particle size distribution between 45 and 80 μm. Figure 19 (As shown), for later use.

[0078] (4) Take the following components in the following proportions: 3 parts by weight of aluminoferrite mineral powder and 6 parts by weight of the regulator described in this embodiment. Wherein, the aluminoferrite mineral is composed of Ca2Al 0.21 Fe 1.79 O5, Ca2Al 0.6 Fe 1.4 O5 and Ca2Al 1.07 Fe 0.93 The mixed powder formed by O5 in a mass ratio of 1:1.5:2 has a specific surface area of ​​526.4 m². 2 / kg. Place all the above components in a mixer and mechanically mix for 3 minutes to obtain a high-compliance concrete shrinkage compensation additive (such as...). Figure 20 (As shown).

[0079] Performance testing: The restricted expansion rate and compressive strength of the shrinkage compensation additive prepared in this embodiment were tested using the same method as in Example 2 above. The results are shown in the table below. A negative restricted expansion rate indicates that volume shrinkage has occurred.

[0080] Example 8: A method for preparing a high-matching concrete shrinkage compensation additive, comprising the following steps: (1) Mix polycarboxylate superplasticizer and sodium lignosulfonate in a mass ratio of 0.3:0.1 and grind them into powder to obtain a composite modifier for later use.

[0081] (2) Add 0.5% by weight of the composite modifier to the dihydrate gypsum (desulfurized gypsum) powder and stir evenly. Then heat to 120°C and keep warm for 20 minutes, then raise the temperature to 160°C and keep warm for 50 minutes. After completion, cool rapidly to room temperature in air to obtain β-type modified hemihydrate gypsum for later use.

[0082] (3) The β-type modified hemihydrate gypsum and anhydrous gypsum (natural hard gypsum) powder were mixed at a mass ratio of 1:2 and stirred evenly to obtain a mixed powder with a particle size distribution between 45 and 80 μm. Then, polyethylene glycol (PEG-400) was sprayed into the mixed powder (PEG-400 was 1.0% of the mass of the mixed powder), and stirred in a mixer at a speed of 1500 rpm for 20 min. After completion, the product was transferred to a sealed container and allowed to stand for aging for 24 hours to obtain the modified regulator (such as...). Figure 21 (As shown), for later use.

[0083] (4) Take the following components in the following proportions: 3 parts by weight of aluminoferrite mineral powder and 6 parts by weight of the modifier described in this embodiment. Wherein, the aluminoferrite mineral is composed of Ca2Al 0.21 Fe 1.79 O5, Ca2Al 0.6 Fe 1.4 O5 and Ca2Al 1.07 Fe 0.93 The mixed powder formed by O5 in a mass ratio of 1:1.5:2 has a specific surface area of ​​526.4 m². 2 / kg. Place all the above components in a mixer and mechanically mix for 3 minutes to obtain a high-compliance concrete shrinkage compensation additive (such as...). Figure 22 (As shown).

[0084] Performance testing: The restricted expansion rate and compressive strength of the shrinkage compensation additive prepared in this embodiment were tested using the same method as in Example 2 above. The results are shown in the table below. A negative restricted expansion rate indicates that volume shrinkage has occurred.

[0085] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-compliance concrete shrinkage compensation additive, characterized in that, The product comprises the following components in the following proportions: 3-20 parts by weight of aluminoferrite mineral powder and 6-26 parts by weight of a modifier; wherein the modifier is composed of microparticles formed from β-type modified hemihydrate gypsum, an anhydrous gypsum core, and polyethylene glycol loaded on the surface of the core, and the β-type modified hemihydrate gypsum contains a portion of its Ca... 2+ K + and / or Al 3+ Lattice distortion resulting from substitution.

2. The high-matching concrete shrinkage compensation additive according to claim 1, characterized in that, The aluminoferrite minerals consist of Ca2Al with gradually increasing aluminum content. 0.21 Fe 1.79 O5, Ca2Al 0.6 Fe 1.4 O5 and Ca2Al 1.07 Fe 0.93 O5 composition; or, the Ca2Al 0.21 Fe 1.79 O5, Ca2Al 0.6 Fe 1.4 O5, Ca2Al 1.07 Fe 0.93 The mass ratio of O5 is 1~2.5:1.5~3.5:2~4.

3. The high-matching concrete shrinkage compensation additive according to claim 1, characterized in that, The specific surface area of ​​the aluminoferrite mineral powder is not less than 400 m². 2 / kg; or, the particle size of the modified regulator is 45~80μm.

4. The high-matching concrete shrinkage compensation additive according to any one of claims 1-3, characterized in that, The preparation of the modified regulator includes the following steps: (1) After mixing gypsum dihydrate powder and a composite modifier consisting of regulator and sulfate, the mixture is calcined in stages and then rapidly cooled to obtain β-type modified hemihydrate gypsum; the regulator is composed of polycarboxylate superplasticizer and lignin sulfonate. (2) Mix the β-type modified hemihydrate gypsum with anhydrous gypsum powder, then mix the resulting mixed powder with liquid polyethylene glycol, and let it stand for aging to obtain the modified regulator.

5. The high-matching concrete shrinkage compensation additive according to claim 4, characterized in that, In step (1), the composite modifier is 0.5-3.0% of the mass of gypsum dihydrate powder; Alternatively, in step (1), the dihydrate gypsum includes at least one of desulfurized gypsum, natural gypsum, phosphogypsum, and titanium gypsum.

6. The high-matching concrete shrinkage compensation additive according to claim 4, characterized in that, In step (1), the mass ratio of the polycarboxylate superplasticizer, lignin sulfonate, and sulfate is 0.3~1:0.1~0.5:0.2~1.

0.

7. The high-matching concrete shrinkage compensation additive according to claim 4, characterized in that, In step (1), the lignin sulfonate includes at least one of sodium lignin sulfonate and calcium lignin sulfonate; Alternatively, in step (1), the sulfate includes at least one of aluminum sulfate and potassium sulfate; Alternatively, in step (1), the staged calcination process includes: first preheating and dehydrating at 120~140℃ for 10~20min, and then raising the temperature to 160~180℃ and holding for 30~50min. Alternatively, in step (1), after calcination, the temperature is rapidly cooled to below 60°C.

8. The high-matching concrete shrinkage compensation additive according to claim 4, characterized in that, In step (2), the mass ratio of the β-type modified hemihydrate gypsum to anhydrous gypsum powder is 1~6:2~8; Alternatively, the anhydrous gypsum may include at least one of natural anhydrite and fluorogypsum.

9. The high-matching concrete shrinkage compensation additive according to claim 4, characterized in that, In step (2), the liquid polyethylene glycol accounts for 1.0~1.5% of the mass of the mixed powder; Alternatively, in step (2), the molecular weight of the liquid polyethylene glycol is not greater than 600; Alternatively, in step (2), the settling and aging time is 20 to 24 hours.

10. The application of the high-matching concrete shrinkage compensation additive according to any one of claims 1-9 in concrete materials; or, the additive is 3-15% of the mass of the cementitious component in the concrete material.

Citation Information

Patent Citations

  • Secondary ettringite type expanding agent and preparation method and application thereof

    CN102167536A

  • Metakaolin-phosphorus gypsum enhancement cement-based material shrinkage reducing agent and preparation method thereof

    CN106986573A

  • Modified enhanced water resistant hydrated lime cementing material and preparation

    CN109626939A

  • Concrete containing high-activity slag powder and manufacturing method thereof

    CN112759317A

  • Gypsum building block manufactured by chemical gypsum and industrial waste and manufacture method thereof

    CN1919781A

Cited By

  • High-crack-resistance cement-based composite material and preparation method thereof

    CN122325188A